Training on integrated science learning for science teachers in Nekamese District - Kadek Ayu Astiti; Andam Surianty (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
PKM activities are carried out in partner schools in the form of training for Mathematics and Natural Sciences teachers to overcome the problems they are facing. Some of the obstacles that are being faced are that science teachers still have difficulty applying integrated science learning according to the demands of the 2013 curriculum. The targets to be achieved in the implementation of this PKM program include increasing the professional competence of teachers in implementing integrated science learning. Activities are designed in several stages, namely 1) coordinating with partner schools for implementation time, 2) providing material related to integrated science learning, 3) Mentoring for Natural Sciences teachers in designing integrated science material and 4) program evaluation. This activity was not only attended by Natural Sciences teachers in partner schools but several Natural Sciences teachers in schools around partner schools were also joined. Participants in the activity were Natural Sciences teachers from SMP N 1 Nekamese, SMP N 2 Nekamese, SMP N 4 Nekamese, and SMP N 5 Nekamese. The participants were quite enthusiastic in participating in this activity, seen from the enthusiasm for joining the activity and dynamic discussions